2013
DOI: 10.7556/jaoa.2013.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Low Back Conditions on Depression Outcomes

Abstract: Increased odds of persistent depressive symptoms and increased number of outpatient visits were found in patients with depression and concomitant LBCs 6 months after enrollment into collaborative care management, compared with those in patients with depression and without LBCs. The data suggest that temporally related LBCs could lead to worse outcomes in primary care patients being treated for depression, encouraging closer observation and possible therapeutic changes in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The relationship between these comorbidities and LBP is consistent with prior work suggesting psychological disorders, 2,[24][25][26]34 disturbances of sleep, [21][22][23] obesity, 17 tobacco use, 16,20 and alcohol use 18,19 are associated with LBP. However, these factors were usually examined separately, and two recent reviews 2,34 noted that heterogeneity among studies of LBP made pooling data and study results difficult.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The relationship between these comorbidities and LBP is consistent with prior work suggesting psychological disorders, 2,[24][25][26]34 disturbances of sleep, [21][22][23] obesity, 17 tobacco use, 16,20 and alcohol use 18,19 are associated with LBP. However, these factors were usually examined separately, and two recent reviews 2,34 noted that heterogeneity among studies of LBP made pooling data and study results difficult.…”
Section: Discussionsupporting
confidence: 87%
“…14,15 Comorbid medical conditions may play a part in developing LBP or in LBP progressing to a chronic or recurrent condition. Tobacco use, 16,17 alcohol use, 18,19 obesity, 20 sleep disturbances, [21][22][23] and mental health disorders 2, [24][25][26] have been identified as risk factors for LBP. Furthermore, people with LBP and medical comorbidities of nicotine dependence, 27 psychological disorders, 24,[26][27][28] sleep disturbance, 29 or alcohol use 18 have shown increased risk for LBP becoming chronic or debilitating.…”
Section: Introductionmentioning
confidence: 99%
“… 12 CCM was also associated with significant short-term improvements in depression outcomes in patients with comorbid physical conditions. 13 - 15 Also, a prior study in our institution demonstrated that within CCM, patients with PD were able to achieve remission only 25.0% of the time by 6 months compared with a 54.3% remission rate for patients without PD ( P < .001). 16 …”
Section: Introductionmentioning
confidence: 82%
“…These mood disorders, such as depression, can reveal itself more in patients who have complications. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%